Take the 2-minute tour ×
Physics Stack Exchange is a question and answer site for active researchers, academics and students of physics. It's 100% free, no registration required.

in the context of non-relativistic quantum mechanics I want to show that, for any $A$ and $B$ operators

$$e^{A}e^{B}=e^{A+B} $$

if and only if

$$[A,B]=0$$

I remember my professor told use about looking for a differential equation but I don't remember the details, and I want to be able to prove it. Brute force the series doesn't seem to be a good idea.

Any hint will be appreciated thanks.

share|improve this question

4 Answers 4

up vote 8 down vote accepted

There is no 'only if' because it is not true: \begin{align} e^{A+B} = e^A e^B \end{align} does not necessarily imply $[A,B] = 0$.

One can easily find an example of this using matrices. Here's one: \begin{align} A= \begin{pmatrix} 0 & 0 \\ 0 & 2\pi i \end{pmatrix}, B=\begin{pmatrix} 0 & 1 \\ 0 & 2 \pi i \end{pmatrix}. \end{align} $[A,B] \neq 0$ but $e^{A+ B} = e^A e^B = I$.

Edit: Let me help with the if part, using a differential equation as OP desires. Compute \begin{align} \frac{d}{dt}(e^{t(A+B)}e^{-tA}e^{-tB}), \end{align} and show that it is $0$ if $[A,B] = 0$.

That implies that $e^{t(A+B)}e^{-tA}e^{-tB}$ is independent of $t$. In particular, plugging in $t = 0$ gives $e^{t(A+B)}e^{-tA}e^{-tB} = I$ for all $t$. Then plug in $t = 1$ to get $e^{(A+B)}e^{-A}e^{-B} = I$.

QED.

share|improve this answer
    
I don't think this counterexample is correct: I get exp(A) = I, but I don't get exp(B) = I. –  Colin McFaul Mar 21 '13 at 3:34
    
@ColinMcFaul Actually I get the same as nervxxx. I tried wolfram alpha as well: http://www.wolframalpha.com/input/?i=MatrixExp+%28{{0%2C1}%2C{0%2C2+pi+i}}%29 –  Michael Brown Mar 21 '13 at 5:13
    
@ Colin McFaul then you are doing something wrong. wolframalpha.com/input/… –  nervxxx Mar 21 '13 at 5:13
2  
+1 because this seems to be true --- but on the other hand I think the OP is implicitly asking about Hermitian operators. –  Nathaniel Mar 21 '13 at 5:35
1  
The Taylor expansion of the exponential function shows $1+ 2\pi i\sum_{k \geq 1} (2 \pi i)^{k-1}/k! = 1$. –  Peter Shor Mar 24 '13 at 17:24

I've never heard of trying to find a differential equation to prove this; I've only done by brute forcing the series expansion. That isn't as bad as it sounds. On the one side of the equation you get a single infinite series with terms of $(A + B)^n$. The other side of the equation gives you two infinite series multiplied together, with terms of $A^m$ and $B^l$. Don't make any assumptions about $[A,B]$ yet, and expand everything out until you have all the terms that contain $AB$ and $BA$. You should find that the constant terms and the terms of order $A$ and $B$ all cancel out, which will leave you with your condition for the commutator.

share|improve this answer

Define the function $f(u)=e^{uA}e^{uB}$. If $A$ and $B$ commute, you can take the derivatives of the $f(u)$ as follows:

$$\frac{df(u)}{du}=\frac{de^{uA}}{du}e^{uB}+e^{uA}\frac{de^{uB}}{du}=Ae^{uA} e^{uB}+e^{uA}Be^{uB}$$

$$\frac{d^2f(u)}{du^2}=A^2e^{uA} e^{uB}+2Ae^{uA}Be^{uB}+e^{uA}B^2e^{uB}$$

etc.

Now take the Maclaurin series expansion:

$$f(u)=1+(A+B)u+\frac{1}{2!}(A^2+2AB+B^2)u^2+\ldots=\\ =1+(A+B)u+\frac{1}{2!}(A+B)^2 u^2+\frac{1}{3!}(A+B)^3 u^3+\ldots=e^{(A+B)u}$$

For $u=1$ you get the desired result:

$$f(1)=e^{A}e^{B}=e^{A+B}$$

Also check this:

Baker–Campbell–Hausdorff formula

Matrix exponential

share|improve this answer
    
This shows the if but not the only if... –  Fabian Mar 20 '13 at 20:21

Remember that you are working with operators.

Since

$$e^{A}e^B =(1+\frac{A}{2}+\frac{AA}{3!}+...)(1+\frac{B}{2}+\frac{BB}{3!}+...)$$

and

$$e^{A+B} =(1+\frac{A+B}{2}+\frac{(A+B)^2}{3!}+...)$$.

Try matching the terms up using commutators.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.